Hubungan Sarana Dan Prasarana Perpustakaan Terhadap Motivasi Belajar Siswa Kelas VII MTs NW Sepit - Muhamad Zaril Gapari (Pendidikan Al-Gafari, 2024)
This study aims to determine the relationship between library facilities and infrastructure on the learning motivation of students of class VII in MTs. NW Sepit Keruak District, East Lombok Regency. The research design used in this study is the correlational method, because of the variables to be examined about and the purpose of presenting a picture of the relationship between the variables studied. Data collection techniques used were observation, questionnaire, and documentation techniques. Data analysis techniques used were validity, reliability, and correlation tests. The results of the calculation of the validity of the instrument using the SPSS product moment formula obtained the r count results in the Extraction column which is for sarpras with the results of item 1 = 0.341, as well as the motivation for item 1 = 0. 442, and r Table for N = 42 with a significance level of 5% is 0.304, Tables items 5 and 8 are invalid whether it is the result of motivation or motivation. While the reliability test results used Cronbach Alpha by 0.751 while the learning motivation of 0, 800. A variable is said to be reliable if it gives a Cronbach Alpha value greater than 0.60. Based on the results of research and data analysis conducted, the values obtained for the hypothesis testing using SPSS obtained values for the variable X namely r count = 0.807 with a significance level of 5% (2-tailed) = 0,000> r table = 0.304. While the correlation test results were obtained, it is known that the value of r = 807. That is, which means the relationship between variable X and Y is 0.807. Y and means hipot ESIS which reads a significant link library means good infrastructure to class VII student motivation MTS NW sepit.